Angiotensin-converting enzyme polymorphisms AND Alzheimer's disease susceptibility: An updated meta-analysis. - Xiao-Yu Xin (Public Library of Science (PLoS), 2021)
Background Many studies among different ethnic populations suggested that angiotensin converting enzyme (ACE) gene polymorphisms were associated with susceptibility to Alzheimer's disease (AD). However, the results remained inconclusive. In the present meta-analysis, we aimed to clarify the effect of ACE polymorphisms on AD risk using all available relevant data. Methods Systemic literature searches were performed using PubMed, Embase, Alzgene and China National Knowledge Infrastructure (CNKI). Relevant data were abstracted according to predefined criteria. Results Totally, 82 independent cohorts from 65 studies were included, focusing on five candidate polymorphisms. For rs1799752 polymorphism, in overall analyses, the insertion (I) allele conferred increased risk to AD compared to the deletion (D) allele (I vs. D: OR = 1.091, 95% CI = 1.007-1.181, p = 0.032); while the I carriers showed increased AD susceptibility compared with the D homozygotes (II + ID vs. DD: OR = 1.131, 95% CI = 1.008-1.270, p = 0.036). However, none of the positive results passed FDR adjustment. In subgroup analysis restricted to late-onset individuals, the associations between rs1799752 polymorphism and AD risk were identified using allelic comparison (OR = 1.154, 95% CI = 1.028-1.295, p = 0.015, FDR = 0.020), homozygotes comparison, dominant model and recessive model (II vs. ID + DD: OR = 1.272, 95% CI = 1.120-1.444, p < 0.001, FDR < 0.001). Nevertheless, no significant association could be revealed after excluding studies not in accordance with Hardy-Weinberg equilibrium (HWE). In North Europeans, but not in East Asians, the I allele demonstrated increased AD susceptibility compared to the D allele (OR = 1.096, 95% CI = 1.021-1.178, p = 0.012, FDR = 0.039). After excluding HWE-deviated cohorts, significant associations were also revealed under homozygotes comparison, additive model (ID vs. DD: OR = 1.266, 95% CI = 1.045-1.534, p = 0.016, FDR = 0.024) and dominant model (II + ID vs. DD: OR = 1.197, 95% CI = 1.062-1.350, p = 0.003, FDR = 0.018) in North Europeans. With regard to rs1800764 polymorphism, significant associations were identified particularly in subgroup of European descent under allelic comparison (T vs. C: OR = 1.063, 95% CI = 1.008-1.120, p = 0.023, FDR = 0.046), additive model and dominant model (TT + TC vs. CC: OR = 1.116, 95% CI = 1.018-1.222, p = 0.019, FDR = 0.046). But after excluding studies not satisfying HWE, all these associations disappeared. No significant associations were detected for rs4343, rs4291 and rs4309 polymorphisms in any genetic model. Conclusions Our results suggested the significant but modest associations between rs1799752 polymorphism and risk to AD in North Europeans. While rs4343, rs4291 and rs4309 polymorphisms are unlikely to be major factors in AD development in our research.